Biomechanical evaluation of the stability of extra-articular distal radius fractures fixed with volar locking plates according to the length of the distal locking screw. Issue 8 (11th June 2021) - Oh, Gyung-Hwan; Kim, Hak-Sung; Lee, Jung Il
Abstract: Surgeons usually used short screws to avoid extensor tendon problems during volar locking plate fixation in distal radius fracture. However, the stability according to the length of distal locking screws have not been fully understood. We investigated this issue through finite element analysis and compression test using synthetic radius. Our results demonstrated that the bi-cortical full-length fixation does not contribute to the stiffness increase in the axial compression direction, and a reduction in length of up to more than 50% length can still provide similar stability to full-length screws. Our data can support that surgeon should undersize the distal screw.